Personal computer checker/ Chong Fah Sam - Chong , Fah Sam (2005)
All undergraduate students of Computer Science and Information Technology in University of Malaya are required to do their final year of project. So the students will apply what they had learned in the university to their final year project. This project is to develop an application which is called Personal Computer Checker, PC Checker. This tool is used for administrating the entire computer system either in the local computer or remote computer. It also acted like administrator to help users to administrate their system. Consequently, PC Checker is an "administration tool" that will make users to easier handle the system problems in Windows ME/200/XP operating system. It also makes Windows XP operating system easier in administration. Basically, PC Checker will ac as an "administrator" in the computer system. It will display operating system information and hardware data and specifications. It also display many different types of information about your local machine on the network like software or products in computer which based on WMI Installed Application Classes. Besides, PC Checker will display service currently running on the system computer. Users can only dynamically control the service by the popup menu on the list view. Lastly, it also displays processes currently running on the system computer, which users the started the process, CPU utilization, and memory usage. User can terminate the processes in the local computer or remote computer especially the processes using the large memory usage in the system. The Rapid Application Development (RAD) with prototyping approach was selected for development process because the strengths of both the RAD and Prototyping can be combined in a single project and reduces the risk involved. The Programming languages that are used to develop the system are VB .Net c# and windows API method. Microsoft Windows ME/200/XP has been chosen as the operating system.